2000
DOI: 10.1161/01.res.86.4.408
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Excitation Frequencies on the Epicardial and Endocardial Surfaces of Fibrillating Ventricular Wall of the Sheep Heart

Abstract: Tissue heterogeneities may play an important role in the mechanism of ventricular tachycardia (VT) and fibrillation (VF) and can lead to a complex spatial distribution of excitation frequencies. Here we used optical mapping and Fourier analysis to determine the distribution of excitation frequencies in >20 000 sites of fibrillating ventricular tissue. Our objective was to use such a distribution as a tool to quantify the degree of organization during VF. Fourteen episodes of VT/VF were induced via rapid pacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
204
3
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(228 citation statements)
references
References 35 publications
18
204
3
3
Order By: Relevance
“…However, other work has questioned the chaotic fibrillation hypothesis (45,46). The current prevailing theory (47), supported by a range of mathematical (48)(49)(50)(51)(52)(53)(54)(55)(56), in vitro (57)(58)(59), and in vivo (57,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) studies, is that fibrillation is a complex nonlinear combination of stochastic and deterministic components, such as scroll waves of electrical activity meandering within the ventricular wall. Given this body of evidence, it is apparent that fibrillation is characterized by high-dimensional nonstationary spatiotemporal dynamics that are too complex for current nonlinear-dynamical control techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, other work has questioned the chaotic fibrillation hypothesis (45,46). The current prevailing theory (47), supported by a range of mathematical (48)(49)(50)(51)(52)(53)(54)(55)(56), in vitro (57)(58)(59), and in vivo (57,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) studies, is that fibrillation is a complex nonlinear combination of stochastic and deterministic components, such as scroll waves of electrical activity meandering within the ventricular wall. Given this body of evidence, it is apparent that fibrillation is characterized by high-dimensional nonstationary spatiotemporal dynamics that are too complex for current nonlinear-dynamical control techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between a sustained mother rotor and underlying heterogeneity could result in conduction blocks and a complex spatial distribution of excitation frequencies, leading to VF. 2,18 …”
Section: Possible Mechanisms Of Cardiac Fibrillationmentioning
confidence: 99%
“…Fibrillatory conduction blocks at specific locations in the periphery of the rotor were responsible for the organization of discrete dominant-frequency domains over the ventricular surface. Zaitsev et al 21 performed Fourier analysis of VF in sheep ventricular tissue slabs. They observed that the frequency domain patterns were relatively stable and could persist from several seconds to several minutes.…”
Section: Multiple Wavelet Hypothesismentioning
confidence: 99%